Problems And Prospects of Women Entrepreneurs in Kanyakumari District - Rekha, N (Ushus Journal of Business Management, 2024)
In recent years, however, things have turned around, and women have maintained their positions as prominent figures and sources of entrepreneurial inspiration. Women nowadays are multi-talented; they have positions in academia, the classroom, politics, software development, business management, banking, civil service, the Indian Administrative Service (IAS), and more. Female company owners are branching out from one kind of enterprise to another. Typically, they would be found in the beauty product, salon, shop, restaurant, etc. industries. Nevertheless, things are starting to change as more and more women are venturing into technical fields, professional services, industry, and the food and beverage sector. The emphasis of women in bygone eras was on the family, and they were married off at a young age. The current research primarily focuses on the difficulties encountered by female entrepreneurs, namely the obstacles and possibilities these women encounter, as a result of the general public’s lack of understanding about technical advancements, marketing strategies, etc. The study’s goals were to(1) determine the socioeconomic status of the population,(2) determine the variables that encourage women to start their own businesses,(3) catalog the difficulties and opportunities faced by female entrepreneurs in the Kanyakumari District, and(4) draw conclusions about these topics.